(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2017)
The hyssop essential oils have been widely used as bactericidal, fungicidal, antivirus and insecticidal agents. On the other hand, the main method to control bacterial contamination is using synthetic bactericide, but the development or conjugation of bacteria resistance to chemical products, the high operational cost and environmental pollution have created the need for developing alternative approaches to control many microbial contamination, especially bacterial and in this sense the essential oils of hyssop is an alternative to control many pathogenic bacteria. Because of a growing concern about relationships between diet and diseases and a growing need to improve the quality and safety of food supply, research is to define conditions that minimize the levels of microbial effect compounds wheat germination and growth. Essential oil of hyssop (Hyssopus officinalis) revealed one of the best biological compounds which control the pathogenic fungal, viral, bacterial and insect contamination. The results of this experiment displayed essential oils were fully effectiveness on bacterial inoculant and support the growth of wheat grain. It capable to eliminated the all pathogenic bacteria which inoculated with seeds. The experiment displayed that bacterial inoculant effected on seed germination, only two varieties of wheat capable to geminate with Pseudomonas inoculated that was 40% in Ghory cultivar and 80% in Sulh variety. Thus shown bacterial inoculated able to decrease 60 and 20 percentage germination of the Ghory and Sulh varieties. Although in all other wheat cultivars hadn’t germination in bacterial inoculated variant, but in controls (inoculant of water, inoculated with essential oil of hyssop) had 100% germination and also in treated variants had > 80% germinated and were greatly treated by essential oil of hyssop (Hyssopus officinalis). Key word: essential oils, environmental pollution, bacterial inoculant, wheat grain, hyssop.